2020
DOI: 10.1038/s41366-020-0564-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcipotriol and iBRD9 reduce obesity in Nur77 knockout mice by regulating the gut microbiota, improving intestinal mucosal barrier function

Abstract: Objective The orphan nuclear receptor Nur77 is an important factor regulating metabolism. Nur77 knockout mice become obese with age, but the cause of obesity in these mice has not been fully ascertained. We attempted to explain the cause of obesity in Nur77 knockout mice from the perspective of the gut microbiota and to investigate the inhibitory effect of calcipotriol combined with BRD9 inhibitor (iBRD9) on obesity. Methods Eight-week-old wild-type mice and Nur77 knockout C57BL/6J mice were treated with calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…e previous study showed Nur77 knockout mice became obese accompanied with the relative abundances of increased Rikenellaceae [33]. At the same time, the abundance of Rikenellaceae was positively correlated with the hepatic inflammation [34].…”
Section: Discussionmentioning
confidence: 92%
“…e previous study showed Nur77 knockout mice became obese accompanied with the relative abundances of increased Rikenellaceae [33]. At the same time, the abundance of Rikenellaceae was positively correlated with the hepatic inflammation [34].…”
Section: Discussionmentioning
confidence: 92%
“…For the calcipotriol treatment study, four groups were injected intraperitoneally with calcipotriol (60 μg per kg body weight) (SWT-cal, SKO-cal), or vehicle (SWT-veh, SKO-veh) three times a week for 12 weeks. 25 Those four groups feed the standard diet containing 1000 IU kg −1 VD 3 , which was provided by Trophic Animal Feed High-Tech Co., Ltd (Nantong, China) (TP 2230G-A). The chemical structures of VD 3 and calcipotriol, and the schematic diagram of the experimental procedure, are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…6 VD is a fat-soluble steroid hormone, with VD 3 primarily produced by the photochemical conversion of 7-dehydrocholesterol in the skin and also acquired directly through dietary intakes. VD 3 undergoes hydroxylation in the liver by 25-hydroxylase to form 25(OH)D 3 and then is further converted into its hormonally active form, 1,25(OH) 2 D 3 , in the proximal renal tubules by 1α-hydroxylase. 7 This hormonally active form exerts both genomic and non-genomic effects by ligand binding the vitamin D receptor (VDR).…”
Section: Introductionmentioning
confidence: 99%
“…As BRD9-deficient Tregs were also defective in the context of tumor immunity, the authors suggested that small-molecule drugs could be useful to fight cancer. Interestingly, a study by Qingqing Lv et al showed that calcipotriol combined with I-BRD9 can regulate the gut microbiota, improve intestinal mucosal barrier function, and reduce LPS absorption into the blood [ 130 ].…”
Section: Advances In Selective Targeting Of Bcpsmentioning
confidence: 99%